Great expectations? Experimental evidence from schools in Pakistan - Minahil Asim; Ronak Jain; Vatsal Khandelwal (University of Zurich, Department of Economics, 2024)
We study the effect of communicating student-specific teacher expectations on academic performance. We randomize whether students (a) receive high-performance expectations, (b) are additionally paired with a classmate for encouragement, (c) receive information about past performance, or (d) receive no message. Expectations increase math scores by 0.19σ, with especially large effects among students who randomly received ambitious expectations and were predicted to perform poorly. Information provision has comparably large effects (0.16σ), particularly in schools with low parental literacy. However, pairing students only improves scores when peers have similar characteristics. Our findings highlight low-cost, sustainable ways of leveraging teachers to improve performance.
Keywords: D91; D84; I24; I25; C93; D83; 330; Expectations; Information; Peer Effects; Motivation; Performance